The potential of silicon in improving rice yield, grain quality, and minimising chalkiness: a review - Engku Abdullah, Engku Hasmah; Misran, Azizah; Yaapar, Muhammad Nazmin; Yusop, Mohd Rafii; Ramli, Asfaliza (Universiti Putra Malaysia Press, 2021)
Silicon (Si) is a micronutrient that can increase the resistance of certain plants against multiple biotic or abiotic stresses. It is known that Si has a beneficial effect on plant growth, beginning in the soil, which could lead to a good crop yield. Despite its benefits, Si is not listed among the generally essential elements or nutrients for rice production in many countries such as Malaysia. This review discusses the ability to uptake Si and its benefits on rice. Environmental factors affect rice production, and among the factors, high temperature has been shown to disrupt the physiological development of rice grain, which contributes to chalkiness. Chalkiness is an undesirable trait that decreases grain’s value, milling, cooking, and eating quality. The application of Si could ameliorate rice grain quality, thus providing a valuable reference for Si fertiliser use in high-quality rice production. This review also presents an update on the potentials of Si in improving the rice yield and grain quality, including Si’s ability to minimise grain chalkiness. Therefore, it is anticipated that Si applications will increase rice yield and grain quality and help to reduce chalkiness.